A clinical herbal prescription Gu-Shu-Kang capsule exerted beneficial effects on the musculoskeletal system of dexamethasone-treated mice by acting on tissue IGF-1 signalling pathway - Xiao-Li Li; Liang Wang; Ming-Chao He; Wen-Xiong Li; Jia-Li Zhang; Yong-Fang Fu; Yan Zhang (Taylor & Francis Group, 2022)
Context Gu-Shu-Kang (GSK) is a clinical traditional Chinese medicine prescription for the treatment of primary osteoporosis.Objective This study investigates the protection of GSK against dexamethasone (Dex)-induced disturbance of musculoskeletal system in male mice and to identify the underlying mechanism.Materials and methods Male C57BL/6 mice in Dex-treated groups were orally administered (i.g.) with vehicle, low dose (0.38 g/kg), middle dose (0.76 g/kg), or high dose (1.52 g/kg) of GSK for 8 weeks. A control group was designed without any treatment. The quadriceps femoris, tibialis anterior and gastrocnemius were harvested. Molecular expression was determined by RT-PCR and immunoblotting.Results Treatment with GSK enhanced weight-loaded swimming time (from 411.7 ± 58.4 s in Dex group to 771.4 ± 87.3 s in GSK-M) and grip strength (from 357.8 ± 23.9 g in Dex group to 880.3 ± 47.6 g in GSK-M). GSK produced a rise in cross-sectional area of myofibers and promoted a switching of glycolytic-to-oxidative myofiber. The administration with GSK affected expression of muscle regulatory factors shown by the down-regulation in MuRF-1 and atrogin-1 and the up-regulation in myogenic differentiation factor (MyoD) and myosin heavy chain (MHC). GSK stimulated tissue IGF-1 signalling pathway (IGF-1R/PI3K/Akt), not only in skeletal muscle but also in bone associated with the amelioration of trabecular bone mineral density and the improvement of osteogenesis.Conclusions These findings revealed the potential mechanisms involved in the beneficial effects of Gu-Shu-Kang on musculoskeletal system in mice with challenging to dexamethasone, and this prescription may have applications in management for muscle atrophy and osteoporosis triggered by glucocorticoid.